The Effect of Prenatal Gentle Yoga on Sleep Quality and Anxiety Levels in Pregnant Women Trimester III - Sri Wulan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Women who are in pregnancy, especially pregnancy in the third trimester, often experience physical or psychological changes, one of the changes experienced is abnormal sleep quality and anxiety that arises because the time of delivery is approaching, these conditions if not immediately overcome can cause discomfort during pregnancy. Yoga is a complementary therapy that can be applied by pregnant women in overcoming complaints both physically and psychologically. The purpose of the study was to determine how the influence of prenatal gentle yoga on sleep quality and anxiety levels in III trimester pregnant women. The type of research is two group pretest posttest design, namely one group to assess sleep quality and one group to assess the anxiety of pregnant women, which is a sample of III trimester pregnant women with a total of 30 people divided into 2 groups, purposive sampling techniques, research at the Maternity Clinic kasih Ibu Galang, measuring instruments using questionnaires and measuring results are tested with t tests. The results obtained are the influence of prenatal gentle yoga on the sleep quality of third trimester pregnant women with a p value of 0.029 and there is an influence of gentle yoga on the anxiety level of third trimester pregnant women with a p value of 0.000. It is recommended for mothers, especially those who are pregnant in the third trimester, to be able to take part in prenatal gentle yoga to be able to overcome pregnancy complaints such as difficulty sleeping and anxiety facing childbirth.